The Palgrave Handbook of Creativity at Work (Springer International Publishing, 2018)
This Handbook provides authoritative up-to-date scholarship and debate concerning creativity at work, and offers a timely opportunity to re-evaluate our understanding of creativity, work, and the pivotal relationship between them. Far from being a new arrival on the scene, the context of work has always been a place shaped and sharpened by creativity, as well as a site that determines, where, when, how, and for whom creativity emerges. Structured in four parts - Working with Creativity (the present); Putting Creativity to Work (in an organizational context); Working in the Creative Industries (creative labour); and Making Creativity Work (the future) - the Handbook is an inspirational learning resource, helping us to work with creativity in innovative ways. Providing a cutting edge, interdisciplinary, diverse, and critical collection of academic and practitioner insights, this Handbook ultimately conveys a message of hope: if we take better care of creativity, our creativity will better care for us.